(untitled) (Ustozlar uchun, 2025)
This paper examines the concept of national linguistic corpora and their growing importance in modern linguistics. The study highlights how national corpora serve as systematic, digitized collections of authentic language data that enable the empirical study of vocabulary, grammar, and discourse patterns. Drawing on current international practices, the article analyzes the functions, design principles, and applications of national corpora for linguistic description, lexicography, and language education. Special attention is paid to the role of corpora in preserving linguistic diversity, standardizing orthography, and supporting natural language processing (NLP) technologies. The paper argues that national corpora not only document linguistic reality but also shape future directions in language policy and teaching methodology. The research is based on qualitative analysis of scholarly literature, comparative corpus studies, and the examination of representative corpus projects such as the British National Corpus (BNC), Russian National Corpus (RNC), and Kazakh National Corpus. The findings demonstrate that well-structured national corpora contribute to the integration of linguistic theory with practical language use and facilitate data-driven decision-making in linguistics.